Challenges and Opportunities: Investment Potential for Indonesia's Local Investors as an Impact of the Development of the National Capital City (IKN) of the Archipelago - Herniati, Herniati (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to recognize the challenges and opportunities for local Indonesia investors towards investment potential as an impact of the development of the National Capital City (IKN) of the archipelago. This research is a type of qualitative research, with a normative juridical research approach. Data collection is carried out by the literature study method, which will then be presented in the form of a narrative description. The development of IKN Nusantara is one of the most historic moments in Indonesia, from the original location of the capital city of Indonesia to be placed in the Special Capital Region Province of Jakarta, then moved to East Kalimantan Province. The development of the Nusantara IKN has an impact on investor opportunities in various sectors, one of which is related to renewable energy. However, this investment opportunity should not only be an opportunity for foreign investors, but must also be sought how local Indonesian investors also contribute. Although there are challenges, such as global geopolitical risks, there are a number of great opportunities that can be taken advantage of, including the huge market potential for local investors in Indonesia.